2019
DOI: 10.1016/j.micromeso.2019.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of adsorbent phyllosilicates rule the entrapping ability of intercalated iron-phenanthroline complex towards thiols

Abstract: The interaction of volatile organic sulfur derivatives, such as 1-heptanethiol (C 7 H 16 S), with clay minerals treated with a μ-oxo Fe 3+-phenanthroline 1:1 complex results strongly affected by crystal chemical properties of pristine mineral phases. In particular, two sepiolite clays with different structural features demonstrated significantly different ability to immobilize the Fe 3+-phenanthroline complex at two pH values (pH = 5.4 and pH = 2.3). The most effective binding was obtained with sepiolite with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In previous studies [24,25] it was found that the coordination chemistry of the “active” capturing cation – copper(II) in our case – drives the immobilization properties of the whole material: a proper solid functionalized with a Cu(II) complex, effective in the removal of gaseous NH 3 , can successfully work also for the immobilization of heptanethiol and H 2 S, taking advantage of the strong affinity of Cu(II) to both N and S centers. In some cases, the affinity of a metal ion for a gas species is retained also changing the host material [26] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies [24,25] it was found that the coordination chemistry of the “active” capturing cation – copper(II) in our case – drives the immobilization properties of the whole material: a proper solid functionalized with a Cu(II) complex, effective in the removal of gaseous NH 3 , can successfully work also for the immobilization of heptanethiol and H 2 S, taking advantage of the strong affinity of Cu(II) to both N and S centers. In some cases, the affinity of a metal ion for a gas species is retained also changing the host material [26] …”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the affinity of a metal ion for a gas species is retained also changing the host material. [26] Experimental Methods…”
Section: Discussionmentioning
confidence: 99%
“…36 The amount of Fe +3 Phen adsorbed by sepiolite is much closer to that of kaolinite but, as mentioned, it is affected by mineral structural ordering and ranges between 0.0048 and 0.0152 moles per 100 g of sepiolite. 39 This enhanced uptake of HPT by Kt-Fe 3+ Phen can be explained only by considering a continuous catalytic activity of Fe 3+ toward the oxidation of thiol to disulfide according to the following reaction mechanisms (water molecules were omitted in the formula of the iron compounds for the sake of clarity): This reaction mechanism only in part overlaps those already hypothesized for hybrid montmorillonite and sepiolite. Nevertheless, the available data cannot allow to distinguish if the reaction proceeds through steps ( 2) and (3) or through steps (2bis) and (3bis), namely, if the reoxidized complex is mononuclear or dinuclear or else their mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Different glass containers were prepared to host 50 mg of Kt-Fe 3+ Phen and uniformly spread on the bottom of a Petri dish (diameter = 50 mm), together with a beaker containing 3 mL of HPT. As already experimented with other HCMs, 39,40 this volume is sufficient to ensure vapor saturation even in the case of a high degree of uptake. After fixed times of exposure, ranging between 12 h and 60 days, the samples were removed from the Petri dishes, air-dried for 1 h, and stored in plastic sealed containers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation